Multiparametric MRI in Diagnosis of Parotid Gland Tumor: An Observational Study in 3-T MRI - Sreecharan V.R; Suprava Naik; Nerbadyswari Deep; Amit Kumar Adhya; Preetam Chappity; Sudipta Mohakud; Manoj Kumar Nayak; Ranjan Kumar Patel; Taraprasad Tripathy (Indian Journal of Radiology and Imaging)
Background Preoperative magnetic resonance imaging (MRI) has an important role in the management and prognostication of parotid gland tumors. We aim to evaluate the role of multiparametric MRI in differentiating the major subgroup of parotid tumors.